Oral Cancer in Sulaimani: A Clinicopathological Study - Talabani, Nazar G.; Ahmed, Khadija M.; Faraj, Farouk H. (Sulaimani Journal for Pure and Applied Sciences, 2010)
Oral cancer is one of the most debilitating and disfiguring of all malignancies; it is one of the most frequently occurring cancers in the body. This study is designed to achieve a retrospective and a prospective epidemiological study on oral cancer in Sulaimani city . In the retrospective cases of oral cancer in ten years (1995-2004) were reviewed, and the prospective study included oral cancer cases diagnosed during the study period. Seventy three cases in the retrospective part and 18 cases in the prospective part were recorded. All cases were analyzed according to age, sex, site and histopathological presentation. In the retrospective part, the patients were 44 males and 29 females with male to female ratio 1.5:1. The lip was the most commonly affected site by oral cancer (32 cases 43.84%), followed by tongue (16 cases, 21.92%).The peak onset of oral cancer seen in age groups (51-60) and (61-70) years .Squamous cell carcinoma was the major histopathological version, followed by tumor of salivary gland region. In the prospective part of the study the patients were15 males, and 3 females. Age group (41-50) was the most commonly affected. The lip was the most commonly affected site. The most frequent histopathological type was squamous cell carcinoma. It was obvious that almost all the cases were seen in an advanced stage, the delay was found to be mainly due to ignorance of the patients, and delay in diagnosis and referral by dental practitioners. Lack of information about habitual smoking and drinking, were noticed. Necessity of cancer registry in Sulaimani is suggested.
Keywords: Oral cancer; Squamous cell carcinoma; patients; habits; smoking,and cancerregistry